GENDER ISSUES OF WOMEN IN LABOR MIGRATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the specific issues faced by female migrants in the labor migration process. Due to gender asymmetry, women often face discrimination, sexual violence, and economic exploitation. Their legal protection is weak, and cases of undocumented work make it difficult to defend their rights. The article thoroughly discusses the economic, social, and psychological consequences of these problems. Additionally, the impact on female migrants' family relations, social equality, and personal development is explored. To address these issues, the development of gender equality policies, the establishment of migrant support systems, and strengthening international cooperation are proposed. The article holds scientific significance in the study of migration and gender issues.